Police Power in the Italian Communes, 1228-1326 - Roberts, Gregory (Premodern Crime and Punishment Ser., 2019)
Police are generally thought of as an invention of the modern state, yet policing in medieval Italy had much in common with modern law enforcement. Foreign soldiers - hired as such to ensure their impartiality in enforcing the statutes - patrolled the streets daily, patting down residents for prohibited weapons and raiding homes and taverns for illicit gambling, sometimes on the basis of concrete intelligence. 'Police Power in the Italian Communes, 1228-1326' is the first book to examine focus on how urban governments in medieval Italy one region policed their populations. Focusing mostly on numerous Bologna Bolognese records from the thirteenth and early fourteenth centuries, Roberts demonstrates how police patrols compelled hundreds of residents to appear in court each year and functioned as a political tool to control violence and disorder. Using largely unexplored archival sources, he paints a vivid picture of how city residents experienced police power in everyday life, and challenges both popular and scholarly assumptions about the role of policing in medieval society.